2007
DOI: 10.1007/s11947-007-0040-z
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Quality and Digestibility Characteristics of Resistant Starch-Enriched Pasta

Abstract: Resistant starches (RS) can be used in food industry to enhance the dietary fiber content of different cereal based products such as pasta and bread. The aim of present study was to develop and evaluate the physical and functional properties of starch-based products enriched with RS. The in vitro enzymatic digestibility, cooking properties, and viscometric characteristics (using rapid visco analyzer= RVA) of the pasta products were determined. The results showed that the addition of resistant starches (RS-s) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(66 citation statements)
references
References 22 publications
(26 reference statements)
2
62
0
2
Order By: Relevance
“…Although sweet potato is already documented as a low glycemic (GI \ 55) food, its consumption is limited (Björck et al 2000). Pasta or spaghetti/noodles is getting wide acceptance in many countries as a health food which could slow down the glycemic response and hence of use in the management of Type 2 diabetes and obesity (Gelencsér et al 2008;Nugent 2005). EGI was positively correlated to RDS and negatively correlated to the RS values in the spaghetti (Madhusudhan and Tharanathan 1995;Sandhu and Lim 2008).…”
Section: Estimated Glycemic Index (Egi)mentioning
confidence: 99%
See 1 more Smart Citation
“…Although sweet potato is already documented as a low glycemic (GI \ 55) food, its consumption is limited (Björck et al 2000). Pasta or spaghetti/noodles is getting wide acceptance in many countries as a health food which could slow down the glycemic response and hence of use in the management of Type 2 diabetes and obesity (Gelencsér et al 2008;Nugent 2005). EGI was positively correlated to RDS and negatively correlated to the RS values in the spaghetti (Madhusudhan and Tharanathan 1995;Sandhu and Lim 2008).…”
Section: Estimated Glycemic Index (Egi)mentioning
confidence: 99%
“…They are produced from purified starches of various plant sources and have become popular in several Asian countries as well (Mestres et al 1988;Collado et al 2001). Starch noodles differ in their quality and texture from Asian or Italian pasta/spaghetti, as the latter are made from wheat flour or semolina (Fu 2008), although many fortified pasta and noodle products have been attempted by subsequent researchers with a view to improving the quality (Gelencsér et al 2008;Padalino et al 2011). Although starch noodles have been classified according to the type of raw materials, size of the noodle strands, manufacturing method etc., their quality is decided mainly by the physicochemical properties of the starches (Chen et al 2003a;Tan et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The cooking procedure of Gelencsér et al [21] was followed with slight modifications. Briefly, 25g of pasta were cooked (triplicate) in 250 mL of boiling distilled water to the optimal cooking time which corresponds to the time required to get complete gelatinisation of starch.…”
Section: Pasta Cooking Proceduresmentioning
confidence: 99%
“…The lowest cooked viscosity values obtained with 45 % RSb and followed with 30 % RSb and 45 % RSa or 15 % RSb. Tímea Gelencsér et al (2008) determined viscometric characteristics of the pasta products using rapid visco analyzer (RVA) and reported a significant (p<0.05) reduction in RVA parameters (peak viscosity, trough, breakdown, setback, and final viscosity) of pasta products that were substituted with RS. Also, Baixauli et al (2008b) reported a decrement in viscosity of muffins dough substituted with 20 % RS.…”
Section: Functional Properties Of Tarhanamentioning
confidence: 99%